Activated microglia in ischemic stroke penumbra upregulate MCP‐1 and CCR2 expression in response to lysophosphatidylcholine derived from adjacent neurons and astrocytes. Issue 3 (2nd December 2014) - Inose, Yuri; Kato, Yoichiro; Kitagawa, Kazuo; Uchiyama, Shinichiro; Shibata, Noriyuki
<x xml:space="preserve">Abstract</x> In acute stage of ischemic stroke, the surrounding zone of fresh infarcts is termed penumbra, where microglia are activated in response to damaged cell‐derived proinflammatory mediators. Rescuing penumbra by regulating inflammatory activity would minimize infarct volume, which positively correlates with functional outcome. To elucidate mechanisms by which inflammation occurs in penumbra, we performed immunohistochemical investigations using autopsied human brains affected by acute, subacute and chronic stages of cerebral infarction as well as cell culture experiments using a murine microglia‐derived cell line (BV‐2). In penumbra of fresh infarcts, immunoreactivity for secretory phospholipase A2 group X (sPLA2‐X), which is responsible for the production and release of the proinflammatory mediator lysophosphatidylcholine (LPC), was intensely detected in neurons and astrocytes. Furthermore, immunoreactivities for the LPC receptors G protein‐coupled receptor 132 (G2A) and P2X purinoreceptor 7 (P2X7R), as well as the CC chemokine monocyte chemoattractant protein‐1 (MCP‐1) and its receptor CCR2, were detectable in activated microglia. Prior to cell culture experiments, it was confirmed that BV‐2 cells were immunoreactive for ionized Ca2+‐binding adaptor molecule 1 (Iba1), G2A, P2X7R, MCP‐1 and CCR2. Reverse transcription‐quantitative polymerase chain reaction analysis revealed that MCP‐1 and CCR2 mRNA expression levels were significantly increased by LPC stimulation. The LPC‐driven increase in MCP‐1 transcripts was lowered by blockade of G2A or P2X7R or by inhibition of Rho‐associated protein kinase (ROCK) or inhibitor of κBα kinase. The LPC‐driven increase in CCR2 transcripts was lowered by blockade of G2A or P2X7R or by inhibition of ROCK, phosphatidylinositide 3‐kinanse, extracellular signal‐regulated kinase kinase, or p38 mitogen‐activated protein kinase. The present results provide in vivo and in vitro evidence that in acute stage of ischemic stroke, the sPLA2‐X enzyme product LPC is released from neurons and astrocytes and stimulates penumbra microglia via G2A and P2X7R, thereby exerting the MCP‐1/CCR2‐mediated neurotoxicity through distinct cell‐signaling pathways.